SEIR Model for Tracking Covid-19 Outbreak - Pasam PrudhviKiran, Dr. E. Laxmi Lydia,Dr.T. Pavani (International Journal of Advanced Science and Technology, 2020)
China was identified as the initiative of 2019-2020 Coronavirus a widespread disease. The first case in India was reported on 30 January 2020. Scientists and doctors signify that the testing rate in India was low when compared to the large number of infections all over the world. India has accounted COVID-19 infected rate to 1.7, very much lower to worst affected countries.The emergence of Simulation studies is set to transform almost every aspect of daily life by provoking us to develop various prediction algorithmswith best possible computation time, without significantly sacrificing the output accuracy. Here in this proposed system, Simulation studies are going to play a big role in our effort to define a pandemic disease such as covid-19 scenario prediction. It is very important to understand the severity and containment of pandemics, to achieve this we focus on developing an efficient simulation model which uses techniques of Artificial Intelligence to learn and accurately predict.